A condição periférica: uma crítica da economia política do espaço em paralaxe - Thiago Canettieri de Mello e Sá (2019)
This thesis is a reflection on the present moment of reproduction of capital that seems to engender a specific moment, a sort of new time of the world, in which the front of defense for the survival of capitalism is not restricted only to the factory, but rather, explodes and implodes, reaching the entire space. This moment generates, in my view, a specific form of (i) production of space, marked by precariousness; (ii) reproduction of daily life, carved by a damaged life in the administered world; (iii) creating the social domination that today reaches all spheres of life today. Faced with this confluence historically determined I suggest to call peripheral condition the predicament that seems to overdeterminate the perpetuation of capital in the world today. The purpose of this thesis is to contribute to the critical understanding of contemporary reality, especially when a diagnosis of bankruptcy of criticism becomes more or less widespread. In this way, some of the categories of the critique of political economy developed by Karl Marx are revisited to try to approximate the concept of what escapes him by the movement of history itself. I will argue in the sense of exposing a cunning of capital that is created, in its automated movement, a form of unprecedented domination. Reconfiguring these categories led me to reflect, therefore, on the conditions of possibility for a perpetual movement of capital, revisiting crisis theory in order to stir up the idea of an infinite crisis. For that reason, I seek to highlight the relevance of the peripheral condition for an interpretation of the present time, going through a critique of the philosophy of history and a critique of the emancipatory praxis to indicate that "there is no easy way out": the forms of mediation that have been torn to this point are in dissolution without anything appearing in its place, in a disordered dialectic, except, of course, for social regression, precariousness and violence, facts that have always been in the peripheries, but now appear as a funeral tone that extends worldwide.